2018
DOI: 10.1002/anie.201807717
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Hydrogen Production by Anodic Oxidation of Primary Amines over a NiSe Nanorod Electrode

Abstract: For electrocatalytic water splitting, the sluggish anodic oxygen evolution reaction (OER) restricts the cathodic hydrogen evolution reaction (HER). Therefore, developing an alternative anodic reaction with accelerating kinetics to produce value-added chemicals, especially coupled with HER, is of great importance. Now, a thermodynamically more favorable primary amine (-CH -NH ) electrooxidation catalyzed by NiSe nanorod arrays in water is reported to replace OER for enhancing HER. The increased H production can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
281
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(291 citation statements)
references
References 62 publications
5
281
0
5
Order By: Relevance
“…Electrochemical water splitting is considered as a promising strategy for converting clean electricity into chemical energy . Water oxidation, one of the half reactions of water splitting, is the pivotal process because of its unfavorable thermodynamics and sluggish kinetics . Thus, the design of efficient, stable, and cheap oxygen evolution reaction (OER) electrocatalyst is an ongoing challenge.…”
mentioning
confidence: 99%
“…Electrochemical water splitting is considered as a promising strategy for converting clean electricity into chemical energy . Water oxidation, one of the half reactions of water splitting, is the pivotal process because of its unfavorable thermodynamics and sluggish kinetics . Thus, the design of efficient, stable, and cheap oxygen evolution reaction (OER) electrocatalyst is an ongoing challenge.…”
mentioning
confidence: 99%
“…In a recent example, Zhang's group employed CoP and NiSe as the cathode and anode, respectively, and constructed a hybrid electrocatalysis system for boosting H 2 production via anodic oxidation of primary amines. [75] NiSe nanorod (~15 nm in diameter) arrays growth on Ni foam (Figure 6a-d) were prepared by direct selenization of commercially available Ni foam under hydrothermal conditions. Figure 6e showed the LSV curves recorded in 1.0 M KOH over the NiSe electrode in the presence and absence of benzylamine (chosen as the model primary amine substrate), respectively.…”
Section: Coupling Her With Amine Oxidation Reactionsmentioning
confidence: 99%
“…Complexes 1-3 were prepared according to the literature procedures. [29,30] (9), Si1-Fe1-H1 92.40 (9) well as elemental analysis. In the IR spectrum of 4, a typical Îœ (Fe-H) stretching band was found at 1839 cm −1 .…”
Section: Synthesis Of [Psip]-pincer Iron Hydrides 1-4mentioning
confidence: 99%
“…It was also found that primary amides could transfer to the related nitriles by ZnCl 2 in CH 3 CN/H 2 O medium under microwave irradiation. [27] After we have studied the dehydration of amides to nitriles with hydrido iron or cobalt complexes as catalysts, [7][8][9][10][11][12][13][14][15][16][17][18]28] now we want to know if Lewis acids can promote these catalytic systems. Therefore, in order to expand the scope of the application of these hydrido iron complexes, four [PSiP]-pincer iron hydrides 1-4 were synthesized ( Figure 1) and their catalytic activities for dehydration of amides to nitriles were explored.…”
Section: Introductionmentioning
confidence: 99%